Experimental analysis and micromechanical models of high performance renewable agave reinforced biocomposites. (15th June 2017) - Zuccarello, B.; Scaffaro, R.
Abstract: The present work deals with the experimental study of high performance biocomposites reinforced with optimized agave fibers, as well as the successive implementation of reliable micromechanical models that can be used at the design stage. In detail, systematical experimental analyses performed on biocomposites with epoxy or PLA matrix, have permitted to highlight that for short fibers biocomposites the reinforcing leads to a significant improvement of the matrix stiffness, whereas the particular damage mechanism based essentially on the matrix failure with consequent tensile failure of the fibers aligned with the applied load, does not allow to obtain an actual reinforcing of the matrix. Such a result is strictly related to the limited fiber stiffness, that lead to a low reinforcing of the matrixes. Consequently, as confirmed by the experimental evidence, the mechanical performance of such biocomposites is not affected significantly by the improvement of the matrix-fiber adhesion provided by the mercerization. Also, the best results are obtained by using the stiffer agave marginata fibers, extracted by simple mechanical pressing of the leafs, without any successive treatment. For long fiber biocomposites, instead, the experimental analysis has shown that for a given fiber treatment, the use of the more deformable PLA allows a better exploiting of the fiber properties, i.e. it leads always to more eco-friendly biocomposites with higher mechanical strength. Moreover, the use of the agave marginata permits to obtain biocomposites with strength higher than the biocomposites reinforced with the common agave sisalana (sisal), with improvements until to about 50%; also, the use of fibers extracted by simple leafs pressing, allows the user to obtain high performance renewable biocomposites, characterized by high stiffness and strength comparable with that obtained by using mercerized fibers. Finally, the detailed analysis of the damage mechanisms, performed also by proper 2D and 3D micrographs, has permitted to implement accurate theoretical models that allows the user accurate predictions of the mechanical performance of biocomposites reinforced with short fibers or long fibers.